Rancang Bangun Sistem Pengukur Konsentrasi Larutan Tembaga Sulfat (CuSO4) Menggunakan Komputer - Sumariyah, Sumariyah; Endro Suseno, Jatmiko; L, Fitria (BERKALA FISIKA, 2007)
A system of Sulphate Copper (CuSO4) liquid consentration measurement by using compute has been made. The display of it through monitor in the computer with the limitation of measurement 0.1 M to 1M. The main components of the measure system of Sulphate Copper (CuSO4) liquid consentration are : tungsten filamen light which include in the sample and photodioda light sensor also IC 741 as a Operational Amplyfier to strengthen the tension of sensor output. As the chage of the output analog signal power tobe digital signal ADC 0809 is used. And also as an interfce which is the pheripheral instrument of communication equipment with computer is used PPI 8255. The software on this measure system uses Turbo Pascal version 7.0. This system had been realized and can measure the Sulphate Copper (CuSO4) liquid consentration wich the linier regresion equal is , with X hole is the sample consentration (M) and Y hole is the measure result of the concentration (M) and the deviation is 0.0326.